El presupuesto en el gobierno autónomo descentralizado parroquial de San José del Tambo periodo 2021. - Alvarado Vásquez, Joselyn Jeaneli (2022)
The Decentralized Autonomous Government (GAD) San José del Tambo, is a public organization, with administrative and financial autonomy dedicated to managing the sustainable and sustainable development of its communities, through its plans and projects established in the annual budget, the The objective of this work is that the inhabitants know the final destination of the economic resources indicated by the Central Regime of Ecuador, through the application of the analysis and use of tools and techniques used, it will proceed to identify if the (GAD) has budgetary controls, In addition, the effective and efficient level of the budget initially assigned for the execution of the budgeted programs will be established. In short, it was specified that the budget allocation is not enough to consider the budget fulfilled in its entirety.